STRATEGY OF DISTRIBUTION VARIATION TO VOLUME OF LIGHT FOOD SALES ON MANDALA TRADING COMPANY IN CIPAKU-CIAMIS REGENCY - Tazkiyah Ainul Qolbi; Rohimat Rudiansyah; Suci Sulastri (Syari'ah Economics, 2021)
This research was conducted to find out the influence of distribution channel cost to sales volume. This research was conducted on a snack food company that survived since 1992 until today and has increased from year to year with the marketing strategy it uses. The types of distribution channels used are the Mandala Cipaku Ciamis Trading Company so well that it can increase the productivity of the company. The method of analysis used in this research is descriptive verivikatif method with correlational research method. Sources of data used in this study is secondary data in the form of corporate financial statements of 2017-2020. The author uses two variables, namely the variable X as the independent variable is the cost of disstribusi channel and variable Y as the dependent variable is the sales volume. Statistical analysis method used by writer is Kolmogorov Smirnov normality test and Simple Linear Regression by testing the hypothesis used is Coefficient of Determination (R2) and Test t (Partial Test). Based on the research results, it can be concluded that: The cost of distribution channels and sales volume of PD Mandala Cipaku Ciamis year 2017-2020 jointly experienced an average increase of 10% achieved the company using the type of distribution channels indirectly by continuing to increase the number of distributors in the cities that are marketing goals. The amount of distribution channel cost incurred by PD Mandala Cipaku Ciamis have a positive and significant effect to the increase of company's sales volume based on the result of quantitative analysis with correlation coefficient value (r) of 0.993 indicates a very strong relationship level, meaning the relationship between distribution channel and sales volume is direction. And the value of determination coefficient (R2) is 98,6% and the rest 1,4% influenced by other factor outside this research. Hypothesis testing using t test shows that the independent variable has a strong and significant influence on the dependent variable.